Morphological variation of two Alexandrium species responsible for paralytic shellfish poisoning in Southeast Asia - Po, T.L; Chui, P.L; Ogata, T. (Walter de Gruyter, 2007)
We examined in clonal cultures the morphological variation of two toxic dinoflagellates, Alexandrium tamiyavanichii and A. minutum, responsible for paralytic shellfish poisoning events in Southeast Asia. The Malaysian strain of A. tamiyavanichii had either a straight or oblique posterior margin on the first apical plate, and a triangular, square to trapezoid-shaped precingular part of the anterior sulcal plate. Morphological variability was also detected in the shape of the first apical plate, its connection to the apical pore, and the position of the ventral pore. In A. minutum, the Malaysian strains showed variation in the sixth precingular plate and the anterior sulcal plate. The length: width ratio of the sixth precingular plate varied from one to two. An anterior sulcal plate with a long left extension also occurred in both of the Malaysian strains. Several characters that have been extensively used in the identification of Alexandrium species have been proven quite variable